High expression of CD133 - stem cell marker for prediction of clinically aggressive type of colorectal cancer - Ognen Kostovski; Svetozar Antovic; Gjorgji Trajkovski; Irena Kostovska; Rubens Jovanovic; Nikola Jankulovski (Fundacja Polski Przegląd Chirurgiczny, 2020)
Background: Colorectal cancer (CRC) is one of the most common malignancies in the world. The cancer stem cell (CSC) markers are associated with aggressive cancer types and poor prognosis. The objective of study was to evaluate the CD133 expression and to correlate it with clinicopathological futures in patients with CRC. Material and Methods: Our study included ninety patients with CRC who underwent curative surgical resection from 2012 to 2017 at the University Clinic for Digestive Surgery, Skopje, North Macedonia. Tumor samples first were analyzed with standard histopathological methods and than CD133 expression was investigated immunohistochemically. The level of expression of CD133 was classified semiquantitatively. Low positivity was defined as positive immunoreactivity in < 50% of tumor glands, and high positivity was defined as positive immunoreactivity in ≥ 50% of tumor glands. Furthermore, clinicopathological futures of patients was retrospective reviewed. Results: High expression of CD133 was found in 47, 8% of patients CRC samples. In 69, 6% of patients with metastatic lesions in visceral organs we found high expression of CD133. We found statistically significant differences in expression of CD133 between patients with and without visceral metastatic lesions (p = 0, 0153), between patients with different T category ((p=0,0119), N-status (p=0,0066) and G-differentiation (p=0,0115). Our results showed that the stage of disease has the greatest impact on expression of CD133 (p <0.00001). Conclusion: High expression of CD133 is useful marker for prediction of clinically aggressive type of CRC and can be routinely implemented in standard pathohistological diagnostics.